2022
DOI: 10.1007/s00268-021-06372-1
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Laparoscopic Versus Open Pancreatoduodenectomy. A Meta‐Analysis

Abstract: Introduction Hybrid laparoscopic techniques have been proposed as a good transition from open to complete minimally invasive approach especially in complex surgical procedures. This meta-analysis aimed to compare the outcomes of hybrid laparoscopic pancreatoduodenectomy versus open pancreatoduodenectomy. Methods A systematic literature research was performed according to PRISMA guidelines. A broad search strategy with terms “laparoscopy” and “pancreatoduod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Previous meta-analyses of comparative studies have consistently demonstrated satisfactory oncologic outcomes, such as R0/R1 resection rates and lymph node yield, following LAPD compared to OPD in patients with malignant conditions [ 43 ]. In terms of oncological outcomes, our study found no statistically significant differences in tumor grade, the number of harvested lymph nodes, or margin status, which aligns with the findings of previous studies [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta-analyses of comparative studies have consistently demonstrated satisfactory oncologic outcomes, such as R0/R1 resection rates and lymph node yield, following LAPD compared to OPD in patients with malignant conditions [ 43 ]. In terms of oncological outcomes, our study found no statistically significant differences in tumor grade, the number of harvested lymph nodes, or margin status, which aligns with the findings of previous studies [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses of comparative studies have consistently demonstrated satisfactory oncologic outcomes, such as R0/R1 resection rates and lymph node yield, following LAPD compared to OPD in patients with malignant conditions [ 43 ]. In terms of oncological outcomes, our study found no statistically significant differences in tumor grade, the number of harvested lymph nodes, or margin status, which aligns with the findings of previous studies [ 43 ]. R0 resection, particularly at critical margins like the retroperitoneal margin and superior mesenteric artery margin, along with a favorable lymph nodal status, are considered the most crucial prognostic factors following PD.…”
Section: Discussionmentioning
confidence: 99%
“…10 While HLPD was associated with significantly longer operating times, it was found to have comparable postoperative outcomes compared to OPD. 17,18 We also emphasize that LPD in this series have been performed in carefully selected patients according to our protocol and the majority of PD are performed via the open approach in our unit.…”
Section: Discussionmentioning
confidence: 99%
“…Permite la resección venosa porto-mesentérica, sin perder el beneficio de la mínima invasión; y 6. Disminuye las complicaciones de la reconstrucción laparoscópica (2)(3)(4)6) . La indicación de PDL empezó restringida para casos muy seleccionados portadores de lesiones pequeñas benignas, premalignas o de bajo potencial maligno, como los quistes pancreáticos o los tumores neuroendocrinos.…”
Section: Discusión La Pancreatoduodenectomía (Pd) Es Una De Las Opera...unclassified
“…La indicación de PDL empezó restringida para casos muy seleccionados portadores de lesiones pequeñas benignas, premalignas o de bajo potencial maligno, como los quistes pancreáticos o los tumores neuroendocrinos. La PDL y PDH han mostrado supervivencias a largo plazo similares a la PDA en neoplasias malignas del páncreas y peri ampulares (6,7) .…”
Section: Discusión La Pancreatoduodenectomía (Pd) Es Una De Las Opera...unclassified